Mrs. Peter Rabbit - Burgess, Thornton W. (Thornton Waldo); Illustrated by Thea kliros (New York Dover Publications, 1996)
When Peter Rabbit convinces Little Miss Fuzzy Tail to marry him and come to live in the Dear Old Briar Patch, he finds true happiness and learns responsibility.
Include Illustrations